2011
DOI: 10.1666/11-047.1
|View full text |Cite
|
Sign up to set email alerts
|

A new asteroid (Echinodermata) faunule from the Early Cretaceous (Barremian) of Morocco

Abstract: An asteroid (Echinodermata) faunule of four taxa representing three surviving families and a probable fourth is described from the Barremian (Early Cretaceous) of Morocco, northwest Africa. The four together suggest limited morphologic evolution since the Cretaceous but biogeographic and depth patterns have changed. Marocaster coronatus n. gen. n. sp. (Valvatida, Goniasteridae) combines apparent derived features of the dorsal disk and superomarginal shape with more stemward expressions of the abactinal ossicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Articulated remains are extremely rare, and are expected to usually happen in storm-generated beds or other kind of rapid deposition events (Hess, 1972;Goldring and Stephenson, 1972;Meyer, 1984Meyer, , 1988Jagt, 2000). For example, Blake and Reboul (2011) reported numerous specimens from Morocco at depths of 30 m or less, in a situation more similar to the case under study here, even though their material came from limestones rather than sandstones. Taking into account that seastars are a conservative group regarding general morphological features (Jagt, 2000), and particularly in the case of Tethyaster (according to Breton, 1996), and given that no significant change is observed in the genus since its first representatives known from the Jurassic (see below), Mesozoic Tethyaster specimens were most likely capable of self-burial as well.…”
Section: Astropectinid Ecology Taphonomy and Palaeoecological Inferesupporting
confidence: 70%
See 1 more Smart Citation
“…Articulated remains are extremely rare, and are expected to usually happen in storm-generated beds or other kind of rapid deposition events (Hess, 1972;Goldring and Stephenson, 1972;Meyer, 1984Meyer, , 1988Jagt, 2000). For example, Blake and Reboul (2011) reported numerous specimens from Morocco at depths of 30 m or less, in a situation more similar to the case under study here, even though their material came from limestones rather than sandstones. Taking into account that seastars are a conservative group regarding general morphological features (Jagt, 2000), and particularly in the case of Tethyaster (according to Breton, 1996), and given that no significant change is observed in the genus since its first representatives known from the Jurassic (see below), Mesozoic Tethyaster specimens were most likely capable of self-burial as well.…”
Section: Astropectinid Ecology Taphonomy and Palaeoecological Inferesupporting
confidence: 70%
“…Known Cretaceous records are mostly European, with other occurrences taking place in Canada, USA and northern Africa (e.g., Blake and Reboul, 2011;Blake and Sprinkle, 1996;Blake and Sturgeon, 1995;Breton, 1996;de Loriol, 1873;Hall and Moore, 1990;Hérenger, 1944;Hess, 1970;Hess and Blake, 1995;Jagt, 2000;Néraudeau and Breton, 1993;Neumann and Hess, 2001;Neumann and Jagt, 2011;Smith et al, 1988;Spencer and Wright, 1966;Villier, 2008;Villier et al, 2007;Vullo et al, 2003). Regarding Lower Cretaceous records, Villier et al (2007) have suggested that the sparseness of astropectinid occurrences could be more related to certain biases rather than being a reflection of low starfish diversity.…”
Section: The Fossil Record Of the Astropectinidae And Palaeobiogeogramentioning
confidence: 99%
“…Many changes to the taxonomic assignments of Blake (1986), Blake and Reid (1998), Blake et al (2000), Blake and Hagdorn (2003), and Blake et al (2006) were proposed by Gale (2005Gale ( , 2011a. All suggestions are rejected here and in Blake & Reboul (2011). Interpretations of Gale (2011a) were not tested through inclusion of fossils in his phylogenetic analysis; perhaps such inclusion would have enabled a single integrated systematic section in his study, rather than division of an inferred single phylogenetic sequence into separate extant and fossil sections.…”
Section: Interpretation Of a Meager But Important Fossil Ecordmentioning
confidence: 96%
“…Benthogenia cribellosa is peculiar in a number of other aspects, perhaps most obvious, the comparatively extended arms, an oddity of uncertain significance found in other Phillippine asteroids (Fisher 1919). Gale (2011a: 57) proposed transfer of Betelgeusia Blake & Reid to the Astropectinidae; radiasterid affinities were reaffirmed in Blake & Reboul (2011).…”
Section: Interpretation Of a Meager But Important Fossil Ecordmentioning
confidence: 99%
“…Taxa recorded from these sites have been referred to the families Astropectinidae, Goniasteridae, and Radiasteridae. Blake and Reboul (2011) also noted a poorly preserved asteroid with affinities to the family Zoroasteridae, but the material did not provide sufficient features to enable a full description.…”
Section: Introductionmentioning
confidence: 99%